1996
DOI: 10.1073/pnas.93.19.10022
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen reduces atherosclerotic lesion development in apolipoprotein E-deficient mice.

Abstract: We have studied the effects of endogenous and exogenous estrogen on atherosclerotic lesions in apolipoprotein E-deficient mice. Female mice ovariectomized (OVX) at weaning displayed increases (P < 0.01) in fatty streak lesions in the proximal aorta and aortic sinus compared with female mice with intact ovarian function. These differences between the OVX and sham controls were apparent in both chow-and "Western-type" diet-fed mice. Moreover, increases in lesion size following OVX occurred without changes in pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
157
5
3

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(179 citation statements)
references
References 43 publications
14
157
5
3
Order By: Relevance
“…The use of these well-defined transgenic models permits a systematic evaluation of the changes at the cellular and molecular level that occur within the lesion, and offers a small animal model in which pharmacologic interventions can be evaluated during the preclinical assessment of compounds that proceed to clinical trials. Using this approach, for example, the effects of estrogen, probucol and the angiotensin II receptor antagonist Losartan 12,32,36 have been evaluated in the apoE knockout, and with probucol, in the LDL receptor knockout. 32 Whereas both Losartan and pharmacologic doses of 17␤-estradiol reduced lesion size in the apoE knockout, probucol actually increased lesion size in both of these models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of these well-defined transgenic models permits a systematic evaluation of the changes at the cellular and molecular level that occur within the lesion, and offers a small animal model in which pharmacologic interventions can be evaluated during the preclinical assessment of compounds that proceed to clinical trials. Using this approach, for example, the effects of estrogen, probucol and the angiotensin II receptor antagonist Losartan 12,32,36 have been evaluated in the apoE knockout, and with probucol, in the LDL receptor knockout. 32 Whereas both Losartan and pharmacologic doses of 17␤-estradiol reduced lesion size in the apoE knockout, probucol actually increased lesion size in both of these models.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10] These cellular responses to exogenous estrogen are consistent with the efficacy of estrogens in preclinical models of atherosclerosis, including the cholesterol-fed rabbit 11 and the apoE knockout mouse. 12 In contrast to the beneficial effects of exogenous estrogens in murine apoE KO and apoE2 transgenic animals, 13 highdose estrogen increases apoB and VLDL synthesis in rats 14,15 and increases total cholesterol in some mouse strains, 16,17 while decreasing cholesterol in others. 18 In the latter 2 studies, chronic estrogen treatment resulted in a shift in cholesterol from HDL to a significant increase in LDL cholesterol.…”
mentioning
confidence: 99%
“…Feeding a diet supplemented with 2% plant phytosterols led to decreases in both total plasma cholesterol and aortic root lesion area [56]. Subdermal 17-␤-oestradiol pellets decreased aortic root lesion area and whole aorta surface lesion area in ovariectomized apoE-deficient mice, and also decreased levels of VLDL cholesterol [57]. Adding 0.5% of an antioxidant, N,NЈ-diphenyl 1,4-phenylenediamine, to a high fat (13%) high cholesterol diet (0.15%) also resulted in decreased aortic lesion surface area, although this drug was associated with increased mortality and failure to gain normal body weight [58].…”
Section: Apoe Deficiency-induced Atherosclerosismentioning
confidence: 99%
“…Although lipoprotein changes occur in premenopausal women and postmenopausal women receiving hormone replacement therapy, in large-scale studies with adjustments for multiple risk factors, only 25-50% of the beneficial effects of estrogen seem to be caused by lipoprotein effects (4). Several large animal species including non-human primate (5), swine (6), and rabbits (7) and, more recently, apolipoprotein E-deficient mice (8,9) have been used to assess these nonlipid effects of estrogen. They showed that effects on endothelium (10,11) may contribute to the cardioprotection observed in humans.…”
mentioning
confidence: 99%